ESTIMATING THE POSSIBLE ROLE OF TESTING CAPACITY AND SOCIAL DISTANCING IN PREDICTING THE GROWTH RATE OF DAILY COVID-19 CASES - Zeeshan Haroon, Muhammad; Khan, Suhaib Ali; Khan, Shahbaz Ali; Khan, Kashif Ali; Khan, Awais Nawaz; Umer Farooq, Muhammad; Aurangzeb, Ahsan (Journal of Ayub Medical College Abbottabad, 2021)
Background: First identified case of the severe acute respiratory distress syndrome corona virus 2 (SARS-CoV-2) was reported in the city of Wuhan, China in December, 2019. The virus quickly spread to the rest of the world leading to an ongoing global pandemic. Globally, various initiatives were set in place, to avoid the further spread of the virus while the world continued to struggle for finding a solution. This study was conducted to estimate the effect of social distancing (days since imposition of a lock-down) and the number of daily tests conducted per million population on the daily growth rate of COVID-19 cases. Methods: After excluding the first 30 days since the announcement of an index case in a country, relevant data for the next forty days was collected from four countries: Belgium, Italy, South Korea and United Kingdom. Two online databases: Our World in Data and worldometer were used for the collection of data which included the number of new COVID-19 cases and the number of tests conducted on a given day. The acquired figures were transformed into per million population of the given country. Growth rate of daily COVID-19 cases was derived and was used as the regress and in a multiple linear regression with number of tests per million population per day and the number of days since a lock-down was imposed as the regressors. Results: It was found that the growth rate of daily COVID-19 cases decreased by .051% when the number of daily tests conducted per million population increased by 1. A .532% decrease in the growth rate of daily COVID-19 cases was observed with each passing day of a lock-down, which essentially represented the most effective form of social distancing. A significant regression was calculated (F(2,155) = 35.191 , p =.014), with an R2 of .054. Neither the daily number of tests conducted per million population nor the number of days of maintaining social distancing (lock-down) were individually significant contributors to the prediction of the growth rate of daily COVID-19 cases (p=.267 and p=.554 respectively). Conclusions: Extensive and rapid increase in the daily number of testing capacity and maintaining social distancing can decrease the growth rate of daily COVID-19 cases. Depending on the availability of the required resources, timely implementation of these measures can lead to better outcomes for a given population. Keywords: COVID-19, SARS, Social Distancing, Pandemic, Corona Virus